Cultural Preservation And Religious Control On Regulating Of The Form And Use Of The Public Space - Said Mahathir (Arsitekno, 2016)
Abstract In the new era of globalization, people are much more aware of the uniqueness and specialty of theirown culture. Banda Aceh, a capital city of Aceh province in Indonesia, which has concerned about this issue in thelast twelve years in preserving their own culture through injecting Sharia law (Islamic law) into constitutional law,so called Qanun. Since Qanun regulates the governance and public life, many aspects either physically or nonphysicallyhas been influencedsince, includinghow to useand behave inthe public space.There are significant differences in controlling public space of Banda Aceh city among the other public spacecontrol in the other cities in Indonesia. Both soft and hard control mechanism are developed such as, 1) dresscode, illicit relationship, gambling, and drinking prohibition in the public space including the punishment areposted; 2) surveillance and policing by Sharia police; 3) public space facilities possibly to be designed to preventfrom unacceptable behavior within Muslim society; and 4) limited access and territory for some religious or cultural reasons. However, these unique public space control possibly have potential impacts on certain attributesin the public space, for instance, different controls have different impact on a certain group of people or differentkind of public space within the city.This paper will first discuss the history of public space development, the typology of existing public space,their functions and activities in Banda Aceh city. Secondly, how these space are regulated pre- and post – Sharialaw and how the law potentially affected the design and use of public space by different social group will beexplored. The methodologies of this research include document review, direct observations on public space and apilot survey study on people’s attitude toward the law. The results of this research hope to serve basic informationfor planners and designers on how to design, plan and regulated the public space for Muslim communities such asBanda Aceh city.Keywords: Sharia law, public space regulation, cultural – based design